When words kill: Islamic legal reflections on cyberbullying-induced suicide - Ismail, Ahmad; Che Adnan, Atif; Mohd Noor Be, Nur Iylia; Mohammad Masruh, Muhammad Luthfi (Journal of Islamic, Social, Economics and Development, 2025)
This article explores the phenomenon of cyberbullying that leads to the victim’s death, particularly suicide driven by severe psychological distress, especially in light of the emergence of artificial intelligence (AI), which has increased the potential for anonymous, automated, and large-scale digital abuse, all examined through the lens of Islamic law. The study adopts a qualitative approach using content analysis of Islamic legal sources such as the Qur’an, Hadith, and the opinions of scholars from major schools of thought. The main focus is to determine the classification of this crime within the Islamic legal framework and the appropriate form of punishment for perpetrators of digital bullying. The findings reveal that death resulting from cyberbullying does not warrant the application of qisas punishment due to the presence of doubt (syubhah) in the evidentiary process, which nullifies the imposition of qisas, just as it does with hudud punishments. Therefore, cybercrimes that culminate in suicide should be addressed through diyah or ta'zir punishments, which grant judicial authorities the discretion to impose penalties based on public interest and contemporary needs. This study highlights the necessity of contemporary ijtihad in dealing with digital crimes in line with the principles of justice and prevention in Islamic law.